2013
DOI: 10.1017/s0263574713000611
|View full text |Cite
|
Sign up to set email alerts
|

Vision-based autonomous hovering for a miniature quad-rotor

Abstract: International audienceIn this paper, a vision-based scheme for the autonomous hovering of a miniature quad-rotor is developed. Cameras are used to estimate the position and the translational velocity of the vehicle. The dynamic model of the miniature quad-rotor is developed using the Newton-Euler approach. A nonlinear controller based on a separated saturation control strategy for a miniature quad-rotor is presented. To validate the theoretical results, an embedded control system for the miniature quad-rotor h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Loianno et al have shown that the very promising embedded software developed in the framework of the tango project could lead to an efficient stabilization of a quadrotor as well as creating 3D maps ( [10]). Recent studies have proposed various vision-based control strategies to make a quadrotor able to follow a line ( [11], [12]), to hover ( [13], [14]), land automatically in a safe place ( [15]) and track a moving robotic platform with active markers ( [16], [17]). Unlike studies based on a fixed camera, we propose here a new approach where a novel visual sensor allows a small quadrotor to locate and track a non-emissive moving target with only 24 pixels.…”
Section: Introductionmentioning
confidence: 99%
“…Loianno et al have shown that the very promising embedded software developed in the framework of the tango project could lead to an efficient stabilization of a quadrotor as well as creating 3D maps ( [10]). Recent studies have proposed various vision-based control strategies to make a quadrotor able to follow a line ( [11], [12]), to hover ( [13], [14]), land automatically in a safe place ( [15]) and track a moving robotic platform with active markers ( [16], [17]). Unlike studies based on a fixed camera, we propose here a new approach where a novel visual sensor allows a small quadrotor to locate and track a non-emissive moving target with only 24 pixels.…”
Section: Introductionmentioning
confidence: 99%
“…This is the main strategy used in sensor-fusion systems. Similarly to Gomez-Balderas et al [7], Saripalli and Sukhatme [8] combined vision with differential GPS for estimating the relative pose of the UAV with respect to the helipad. In this work, geometric invariant extraction is used to identify a H-shape landing pad.…”
Section: Related Workmentioning
confidence: 99%
“…Vision combined with structured environments has been applied successfully in hovering control [ 4 , 5 , 6 ]. For instance, an autonomous quadrotor aircraft can perform stable hovering above a pattern glyph with a data-fusion algorithm using both visual system measurements and inertial sensors [ 6 ]. However, the vision system relied on the pattern glyph, which is specially designed to align the aircraft with the glyph.…”
Section: Introductionmentioning
confidence: 99%